2017
DOI: 10.1093/sleep/zsx085
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Adult Sleep Behavior Over 20 Years—The Population-Based Doetinchem Cohort Study

Abstract: Study Objectives:To describe sleep duration patterns of adults over a 20-year period; to compare sociodemographic, lifestyle, and health characteristics across these patterns; and to relate the patterns to sleep quality.Methods:The study population consisted of 3695 adults aged 20 to 59 years at baseline. Five measurements of self-reported sleep duration were used to compose seven patterns from 1987 to 2012: persistent short (≤6 hours), moderate (7–8 hours), or long (≥9 hours) sleep duration and several changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
21
0
2
Order By: Relevance
“…The average nocturnal sleep duration is less than 7 hours in our subjects, which is shorter than that reported in other countries like the United States [,] and European countries [37]. In fact, at least 7 hours of sleep is recommended by the US Centers for Disease Control and Prevention to promote optimal health [38].…”
Section: Discussionmentioning
confidence: 69%
“…The average nocturnal sleep duration is less than 7 hours in our subjects, which is shorter than that reported in other countries like the United States [,] and European countries [37]. In fact, at least 7 hours of sleep is recommended by the US Centers for Disease Control and Prevention to promote optimal health [38].…”
Section: Discussionmentioning
confidence: 69%
“…Similar results were found in a Canadian study ( Chaput et al, 2017 ). In a 20-year prospective investigation, the authors identified that individuals who had persistent short sleep (≤6 h) or who became short sleepers during the follow-up were more likely to report poorer sleep quality than were those who reported persistent moderate sleep (7–8 h) ( Zomers et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… 140 , 141 Alcohol is also associated with exacerbation of snoring and OSA. 140 Physical inactivity has been associated with reduced self-reported hours of sleep 142 and increased risk of clinically diagnosed insomnia. 143 Furthermore, there is evidence that increased physical activity improves sleep quality.…”
Section: Psychosocial Aspects Of Pcos and Association With Sleepmentioning
confidence: 99%